Ozyegin University Example: Responsible Consumption & Responsible Stakeholders - Tugba Cubukcu; Ceren Demirci (Journal of Sustainability Perspectives, 2021)
Sustainability has been one of the core principles at Ozyegin University (OzU) since its establishment in 2008 and is deeply embedded in its education, research and governance strategy. For OzU, being a green university means building an organic community constantly improving itself on every aspect of sustainability in collaboration with all its stakeholders. OzU accomplished these by establishing the first Health & Safety and Environment (HSE) Department within a university in Turkey. Besides, OzU is also the first university in Turkey to have been concurrently awarded both ISO 14001 Environmental Management System and OHSAS 45001 Occupational Health and Safety Management System Certifications. With these accomplishments OzU has pioneered the path for sustainable universities in Turkey resulting in various rewards and highest places in multitude rankings including GreenMetric. This paper discusses OzU’s strategy and the subsequent steps taken to attain these achievements including the roles of HSE Department and HSE Board